(untitled) (Nóema, 2014)
The text hereby presented is the result of a Philosophical Seminar in Hermeneutics, held by Prof. Rossella Fabbrichesi at the Università degli Studi of Milan in Fall 2013. All participants devoted their efforts to trying to define what particular kind of practice philosophical praxis can be; secondly, they tried to figure out what significance has the making of philosophy nowadays, in everyone’s personal biography. Thus, the present transcript represents the collective product of a polyphonic dialogue among all the seminar’s participants.